The contents of mobile organic substance by different fertilizer system in organic farming - Чередниченко, І. В. (Scientific Progress & Innovations, 2015)
The study of the effect of various fertilization on the content of moving of typical chernozem organic matter under in conditions of organic farming was presented in the article. We established that typical chernozem under natural vegetation (layland) helps significantly increase the share of organic substances moving within the total humus. The positive impact of the share of mobile organic substance in general is the use of organic and green manure fertilizing systems and the introduction perennial grasses in crop rotation. The use of mineral fertilizer system causes depletion of soil moving organic substance.